The relationship between leadership style, creativity, and competitive advantages among the government officers in the department of housing programs of United Arab Emirates (UAE) - Bintarish Almheiri, Murshid Mohamed Obaid (2024)
The primary purpose of this study was to investigate the effect of leadership styles (transformational leadership, transactional leadership, autocratic leadership, democratic leadership, paternalistic leadership, and Laissez-faire leadership) on competitive advantage in the context of public sector organizations (government housing programs) in the UAE. The study also examined the role of employee creativity as a mediator in the relationship. Questionnaires were distributed to 600 employees working in government housing programs in the UAE. 340 questionnaires were returned, but only 323 were used in the analysis using Structural Equation Modelling (SEM) - Partial Least (PLS) method. The results of the study revealed a significant effect of transformational leadership, transactional leadership, autocratic leadership, democratic leadership, paternalistic leadership, and Laissez-faire leadership, on employee creativity and competitive advantage. In addition, it has been found that employee creativity has a significant relationship with competitive advantage. The results also demonstrated the mediating role of employee creativity in the link between transformational leadership, transactional leadership, autocratic leadership, democratic leadership, paternalistic leadership, Laissez-faire leadership, and competitive advantage. The present study also highlighted the implications of the research, future research recommendations as well as its limitations.